Foreign Bodies Simulating a Congenital Palatal Fistula and Vascular Anomaly - Mekonen Eshete; Fikre Abate; Taye Hailu; Mulualem Gessesse; Azeez Butali (Hindawi Limited, 2015)
Foreign bodies embedded in the palate are uncommon findings and may occasionally mimic oral lesions. In the majority of the cases, foreign body embedment in the palate happens in infants and children who are unable to give history. Physical examination in the oral cavity of this group of patients in order to arrive at a definitive diagnosis is limited. We present two female infants with foreign bodies adherent to the hard palate. The first was ten months old and the second was 11 months old. In both cases the materials removed from the palate were plastic in nature (black or red in color and circular in shape). The first simulated a palatal fistula and the second a vascular anomaly.